2003
DOI: 10.1258/000456303770367289
|View full text |Cite
|
Sign up to set email alerts
|

Feedback from a point-of-care test for nicotine intake to reduce smoking during pregnancy

Abstract: Background Smoking is the most important modifiable risk factor for adverse pregnancy outcome in the UK. New tools are needed to improve smoking cessation advice. The aim was to investigate a point-of-care urine test for smoking, to provide feedback to women, to improve awareness about the effects of smoking during pregnancy and to relate the test results to pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…Furthermore, 45% of the cases had lower salivary nicotine metabolite values at eight weeks compared with only 21% of controls, and only 7% of the cases had higher values compared with 30% of controls. This increase in nicotine intake in the control group is consistent with previous findings using the point of care test 16. These results compare favourably with other reported outcomes for intensive advice on smoking cessation that include follow-up appointments,6 whereas the results for the intervention are significantly better than those from non-pharmacological intervention studies 5 9…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, 45% of the cases had lower salivary nicotine metabolite values at eight weeks compared with only 21% of controls, and only 7% of the cases had higher values compared with 30% of controls. This increase in nicotine intake in the control group is consistent with previous findings using the point of care test 16. These results compare favourably with other reported outcomes for intensive advice on smoking cessation that include follow-up appointments,6 whereas the results for the intervention are significantly better than those from non-pharmacological intervention studies 5 9…”
Section: Discussionsupporting
confidence: 90%
“…Twenty individually randomised controlled trials [35],[37],[38],[41],[43],[45],[46],[48]–[51],[56]–[64], six cluster randomised controlled trials [40],[42],[52]–[55], and four non-randomised controlled trials (which used quasi-randomisation methods) [36],[39],[44],[47] were identified. The majority of studies (n = 20) were conducted in the United States [35]–[38],[41],[43],[45]–[47],[50],[51],[54],[56]–[59],[61]–[64], with five studies conducted in the United Kingdom [39],[42],[49],[53],[60], two in the Netherlands [40],[44], and one study each conducted in Poland [55], Canada [48], and New Zealand [52].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (n = 20) were conducted in the United States [35]–[38],[41],[43],[45]–[47],[50],[51],[54],[56]–[59],[61]–[64], with five studies conducted in the United Kingdom [39],[42],[49],[53],[60], two in the Netherlands [40],[44], and one study each conducted in Poland [55], Canada [48], and New Zealand [52]. The majority of studies used behavioural counselling approaches.…”
Section: Resultsmentioning
confidence: 99%
“…The duration of each intervention varied significantly (see Table 1 ) allowed subjects to participate in the study up to and including the second trimester [3,[18][19][20][25][26][27][28][29] . Eleven of the twenty-four studies either did not specify the time during the pregnancy for the initiation of the intervention or allowed subjects to join the study up until the last 12 weeks of gestation.…”
Section: Initiation and Duration Of Interventionmentioning
confidence: 99%
“…[6,19,20,31] . Computer programs were issued by Campbell et al (2006), Lawrence et al (2003) and Ondersma et al (2011) [17,29,31] . Hajek et al…”
Section: Other Interventionsmentioning
confidence: 99%